Eufrásio de Arruda Câmara: rivalidades e tramas do poder local na Paraíba (1889-1923) - Silva, Doralice Amancio da (2024)
This dissertation text intends to analyze the political disputes in the First Republic, based on the actions of Colonel Eufrásio Cavalcanti de Arruda Câmara. To do this, we will emphasize the main aspects of Paraíba politics, aiming to establish a broader connection about the actions and practices carried out by political groups, which, linked to the power of relatives, influenced State policy. At the municipal level, we will analyze the characteristics of coronelismo through a case study on the trajectory, the events experienced and experienced by the character, the power relations, the conflicts, and the problems related to Fazenda Sapé. We will focus on the case of Alagoa Nova, which was a political dispute for political-administrative control, around the municipality between the Eufrasista x Tavarista factions in 1912 and 1913. To fill the temporal gap, we will survey events shortly after the political dispute , until we reached a narrative about the murder of Eufrásio Câmara, which occurred in 1923. To support the research, we consulted documentary sources, such as printed newspapers with state circulation (O newspaper A União and newspaper O Norte); letters and telegrams available on the Hemeroteca Nacional website and the criminal case relating to the Colonel's murder, available at the Pedro Gondim Forum in Alagoa Nova. From a theoretical-methodological point of view, we adopted the perspective of analysis from a micro-history perspective, based on a set of fragments and ruins, responsible for unfolding aspects of collective, political and social life. Among the reference bibliography to support discussions and political articulations in Paraíba, we resort to (Lewin, 1993), (Rodrigues, 1983), (Queiroz, 1975), (Leal, 2012).